Evaluasi Kinerja Layanan dan Produk pada UMKM Mie Endes Berbasis Kepuasan Konsumen - Andiniatul Maulidia; Resa Ummami; Hanum Hanafia; Ifa Khoirun Nasiroh; Desya Ladyana Lestari; Mochamad Reza Adiyanto (Jurnal bintang manajemen, 2025)
customer satisfaction. Using survey method and questionnaires distributed online, data were collected from 37 respondents who are customers of Mie Endes. The results of the analysis show that most customers are satisfied with the services provided, especially in terms of friendly staff attitudes and responsiveness to complaints. However, there are some aspects that need improvement, such as the speed of response to problems and detailed product information. This study emphasizes the importance of service quality in increasing customer satisfaction and loyalty, and recommends further training for staff and periodic satisfaction surveys to continuously improve MSME performance. Thus, Mie Endes is expected to maintain growth and competitiveness in an increasingly competitive market.